Study on Mechanical Properties of the Expansive Soil Treated with Iron Tailings Sand. (22nd April 2021) - Chu, Chengfu; Zhang, Fei; Wu, Daoxiang; Zhan, Meihuang; Liu, Yun
Abstract : Aiming at researching shear strength parameters of expansive soil modified by industrial waste iron tailings sand, the enhancement of expansive soil is explored from macroscopic and microscopic aspects. After characterization and testing by various means, the results show that expansive soil modified by iron tailings sand will increase the maximum dry density of the improved soil and reduce its optimal moisture content, which is beneficial in tuning the moisture content at the construction site. In addition, iron tailings sand can improve the shear strength of expansive soils. The influence of iron tailings sand on cohesion increases first, then decreases, and reaches the peak value at 30%, while the effect on internal friction angle exhibits a continuously increasing trend. Furthermore, according to mercury intrusion tests and microangle analysis, the addition of iron tailings sand can reduce the tiny pores and enhance the occlusal force of the soil. Simultaneously, it increases the number of large pores, maximizing the macroscopic strengthening of iron tailings sand towards the expansive soil.